What Makes the World Go Round? Some Reformed Perspectives on Pneumatology and Ecology - Conradie, Ernst M. (Journal of Reformed Theology, 2012)
Abstract This contribution explores the available literature on pneumatology and ecology. It suggests the need to articulate the underlying question to which Christian pneumatology may be regarded as a response, namely in terms of 'What makes the world go round?' Moltmann's recent notion of a 'hermeneutics of nature' is used to suggest the possibility of a pneumatology 'from below'. However, the theological inadequacy of available proposals on such a pneumatology from below is also noted. This suggests the need for deeper pneumatological discernment.
Paid
Keywords: DISCERNMENT (Christian theology); ECOLOGY; GOD; HERMENEUTICS; HOLY Spirit; MOLTMANN; Jurgen; 1926-; Moltmann; discernment; ecology; hermeneutics; pneumatology